2019
DOI: 10.14326/abe.8.110
|View full text |Cite
|
Sign up to set email alerts
|

Linear and Nonlinear Analysis of the Carotid Sinus Baroreflex Dynamic Characteristics

Abstract: The arterial barore ex system is an important negative feedback system that controls arterial pressure (AP) within a normal range during daily activities. We have analyzed this system in anesthetized animals. Several issues need to be considered: the presence of physiological and measurement noises that interfere with the system identi cation, the closed-loop nature of the arterial barore ex system, the existence of parallel feedback systems that may modify the system responses, and the presence of nonlinear r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 43 publications
(70 reference statements)
0
4
0
Order By: Relevance
“…S1). BRS was assessed separately during both types of postural changes as supine to stand typically induces a larger BP drop compared to sit to stand, and previous studies reported BRS to behave non-linearly to different degrees of BP drop (Moslehpour et al, 2016;Kawada et al, 2019;Verma et al, 2017).…”
Section: Baroreflex Sensitivitymentioning
confidence: 99%
“…S1). BRS was assessed separately during both types of postural changes as supine to stand typically induces a larger BP drop compared to sit to stand, and previous studies reported BRS to behave non-linearly to different degrees of BP drop (Moslehpour et al, 2016;Kawada et al, 2019;Verma et al, 2017).…”
Section: Baroreflex Sensitivitymentioning
confidence: 99%
“…In each segment, the linear trend was subtracted, and a Hanning window was applied. The transfer function and magnitude‐squared coherence function were computed via standard nonparametric analysis per segment and then ensemble averaged (Bendat & Piersol, 2010; Kawada et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…The input power spectra [ S VNS·VNS ( f )], output power spectra [ S HR·HR ( f )], and cross spectra [ S HR·VNS ( f )] were calculated over the eight segments via Fourier transform. The transfer function from VNS to HR was estimated from the following equation (Equation ) (Bendat & Piersol, 2010; Kawada, Mukkamala, et al, 2019):H)(f=SnormalHR·normalVNS)(fSnormalVNS·normalVNS)(f.…”
Section: Methodsmentioning
confidence: 99%
“…The magnitude‐squared coherence function was also calculated from the following equation (Equation ) (Bendat & Piersol, 2010; Kawada, Mukkamala, et al, 2019):Coh)(f=SHR·VNSf2SVNS·VNS)(fSHR·HR)(f.…”
Section: Methodsmentioning
confidence: 99%